Are the Mechanisms for Assessing the Quality of Training for Graduates of the Russian Penitentiary System Perfect? - Rumyantsev, Nikolay V. (2020)
The relevance of the study is due to the need to assess the quality of training of graduates of the Russian penitentiary system and the lack of an effective tool to assess the quality and level of training of graduates who have mastered professional educational programs at educational institutions of the Federal Penitentiary Service of Russia. In this regard, this article is aimed at identifying or disclosing mechanisms for evaluating the quality of educational services by independent experts, representatives of the employer, through professional and public accreditation of educational programs in educational institutions of the Federal Penitentiary Service of Russia. The leading methods to the study of this problem are general scientific methods (analysis, synthesis, analogy, generalization, etc.), which to introduce allow a comprehensive review of the procedure for professional and public accreditation of educational programs in the system of the Russian Federation. The article reveals the expected results of introducing the institution of professional public accreditation of educational programs in the Russian penitentiary system: improving the quality of the implemented educational programs, the level of organization of staff training, the quality and relevance of educational services, and the image of departmental services. The materials of the article are of practical value for improving the evaluation system of professional educational programs implemented in educational institutions of the Federal Penitentiary Service of Russia.